Pengaruh Pengawasan Langsung dan Tidak Langsung terhadap Efektivitas Kerja Pegawai pada Dinas Pekerjaan Umum dan Pemukiman Prasarana Wilayah Kota Samarinda - Purwadi Purwadi (AKUNTABEL, 2017)
The purpose of this study is to determine the positive effects of direct supervision and indirect supervision and which variables that give dominant influence on the effectiveness of employees. Object in this research is all employee of Department of Public Works and Residential Infrastructure of City of Samarinda. The data were collected by questionnaire. The analysis tool used is multiple linear regression. The results of the study found that all of them were positive, meaning the estimation of the effect between direct supervision (X1) and indirect supervision (X2) together was unidirectional and there was a positive influence.Keywords: supervision, effectiveness of work, Samarinda